2023
DOI: 10.1021/acsaem.2c03988
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Stacked Zn with Abundant Corners for Selective CO2 Electroreduction to CO

Abstract: Electric-driven CO2 reduction offers a promising strategy for CO2 conversion into valuable chemicals and fuels. However, developing low cost and efficient catalysts is still a challenge. Although earth-abundant Zn with the capability of converting CO2 to CO is considered to be one of the promising materials, the low selectivity and stability of Zn catalyst limit its practical applications in CO2 reduction. Herein, we report a highly selective and stable layer-stacked Zn catalyst prepared by an efficient and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…They attributed this observation to the effect of catalyst layer etching, which has previously been observed in aqueous GDE systems. Recently, Zhou et al 124 reported a layer-stacked Zn catalyst with abundant corners that are selective for CO production. By periodically reactivating the catalyst with several anodic oxidation and reduction cycles, the author extended the catalyst lifetime to about 40 h. These promising results highlight the potential of this strategy to enhance the stability of CO 2 conversion systems by some anodic periodic pulsing conditions.…”
Section: Catalyst Surface Reconstructionmentioning
confidence: 99%
“…They attributed this observation to the effect of catalyst layer etching, which has previously been observed in aqueous GDE systems. Recently, Zhou et al 124 reported a layer-stacked Zn catalyst with abundant corners that are selective for CO production. By periodically reactivating the catalyst with several anodic oxidation and reduction cycles, the author extended the catalyst lifetime to about 40 h. These promising results highlight the potential of this strategy to enhance the stability of CO 2 conversion systems by some anodic periodic pulsing conditions.…”
Section: Catalyst Surface Reconstructionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In this process, the anthropogenic carbon cycle can be closed by coupling with renewable electricity. In the past few decades, most of the CO 2 reduction studies have been focused on developing efficient and stable electrocatalysts for selectively converting CO 2 into a desired product through engineering the catalysts such as modulation of crystal facets, 11-13 compositions [14][15][16][17][18][19][20] and morphology 7,[21][22][23] of the catalyst surface. The notable advancements in the enhancement for selectivity and activity of CO 2 electrolysis have been made by engineering the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Zn-based catalysts have attracted much attention for CO 2 conversion due to their low cost, abundant reserves, and accessible CO selectivity, which are considered as a promising alternative to noble metal catalysts. It was reported that ZnO nanosheets fabricated by adjusting alkaline additives and the molar ratios of zinc source/urea showed good CO 2 RR performance .…”
Section: Introductionmentioning
confidence: 99%